Arduino-based Irrigation System for Mung Bean Sprouts Cultivation - Md.Khir, Abraar; Mustafa, Fitri; Ismail, Aliff Alfurqan; Zainal, Zainab (Multidisciplinary Applied Research and Innovation, 2023)
Abstract: Mini Bean Sprout Harvesting System (TAUGEHNATOR) is an automated harvesting controller which is made to eliminate the burden for anyone who ever want to grow bean sprout. Besides that, the aim for this project is to facilitate the assessments on growing the bean sprout. Harvesting method is commonly used among our community in every planting. Following that, harvesting method is chosen to be the central idea on build this system. Provide facility to public is the main idea that guide to our starting progress. Using sprinklers drip, we have designed a system that is ideal for growing the sprout. For implementation of automated plant watering system, we have used combination of water pump, pipes, sprinkler, filter, and water tank. Plus, we introduce our rinse and drain techniques. The waters came out from the sprinkler will spreading among the mung bean spread and the filter will eliminate the excess water and fill the water tank. NodeMcu ESP8266 is the microcontroller that we use as a main controller for this system. It is programmed to monitor the water pump by sending the signal through relay module to control the watering time at particular time. This leads on helping the mung bean seeds to get enough water whenever it getting dry and help to optimize the effectiveness of germinate Mung bean seeds and produce quality sprout. According to our tray size, generally sprout need to be rinse every 5 minutes every one hours.